Konstruksi Persepsi Autentik dalam Konten Endorsement TikTok: Studi Kasus Tante Lala - Muhammad Rivaldy; Kezia Arum Sary; Johantan Alfando W.S; Ziya Ibrizah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines how non-conventional communicative performances construct perceived authenticity in TikTok endorsement content. Using Krippendorff’s qualitative content analysis, the study analyzes verbal and non-verbal communication strategies in high-engagement endorsement videos produced by the Indonesian influencer Tante Lala. Findings indicate that regional dialects, heightened vocal intensity, and theatrical kinesics function as symbolic resources that negotiate authenticity and intimacy with audiences. These communicative performances blur the boundaries between commercial persuasion and interpersonal interaction, generating parasocial relationships that enhance persuasive effectiveness. The study contributes to symbolic interactionism by demonstrating how authenticity in influencer marketing is socially constructed through continuous symbolic negotiation in digital environments.